PERAN UNITED NATIONS CHILDREN’S FUND (UNICEF) DALAM MENANGANI PERNIKAHAN ANAK DI INDONESIA TAHUN 2016 – 2018 - Nida, Rifdah Salsabila Nida; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research aims to analyze the role of the United Nations Children's Fund (UNICEF) in handling child marriage issues in Indonesia for the period 2016 - 2018. Child marriage is a form of violation of children's rights. Marriage before the age of 18 can have negative impacts, especially for girls, such as interrupting education, being vulnerable to experiencing reproductive problems, living in poverty and experiencing domestic violence. As an international organization whose mission is to protect children's rights, UNICEF plays a role in overcoming the problem of child marriage in Indonesia. This study uses a pluralism perspective and international organization theory. The research method used is a qualitative research methods with library research techniques, namely utilizing secondary data obtained through various literature such as books, journals, newspapers, annual reports of several related agencies, websites, or other materials that support research. The results of this study shows that in dealing with the problem of child marriage, UNICEF carries out various programs in collaboration with the government and non-governmental organizations, disseminating information through reports and data releases, and education through various media. Keywords: UNICEF, Child Marriage, International Organization